PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI RESTAURANT JEPANG SUSHI HIRO MALL TAMAN ANGGREK JAKARTA - Fauzi, Andini; Surono, Surono (universitas teuku umar, 2025)
ABSTRACTThis study aims to analyze the influence of Brand Image, Product Quality, and Price Perception on Purchasing Decisions at Sushi Hiro Mall Taman Anggrek, West Jakarta. The data used are primary data, obtained through collecting questionnaires from respondents. The data processing process is carried out using the SPSS version 25 application. The study population includes all consumers who visit Sushi Hiro Mall Taman Anggrek, West Jakarta. The sample taken was 130 respondents, using the Accidental Sampling technique. In this study, the analysis used is multiple linear regression. Several tests were also carried out, including the Classical Assumption Test, F Test, and t Test to test the hypothesis. The results of the study indicate that partially, the Brand Image variable does not have a significant effect on purchasing decisions. Meanwhile, the Product Quality and Price Perception variables have a positive and significant effect on purchasing decisions. Simultaneously, Brand Image, Product Quality, and Price Perception affect purchasing decisions.